'The house was a garbage dump': waste, mess and aesthetic reclamation in 1960s and 70s 'mad housewife' fiction. Issue 3 (3rd March 2020) - Dini, Rachele
ABSTRACT: This article examines the representation of waste and re-use in a selection of 'mad housewife' novels of the late 1960s and 1970s in an effort to redress feminist critics' assessments of the genre as historically important but of dubious literary worth. Focussing on Anne Richardson Roiphe's Up the Sandbox!, Sheila Ballantyne's Norma Jean the Termite Queen, and Alix Kates Schulman's Memoirs of an Ex Prom-Queen, I argue that the novels in this genre enact their protagonists' departure from convention through the adoption of a fluid, collagistic structure that moves between temporal modes, narrative perspectives, and reality and fantasy, and through their incorporation of a range of external media (newspaper excerpts, recipes, advertising slogans) that 'mess up' the tidy structure of the popular realist novels that they seem, at first glance, to emulate. In their relentless attention to literal and figurative waste matter, and through the use of literary devices that defeat the attempt to bind the story within a linear narrative, Roiphe, Ballantyne, and Schulman create a carnivalesque disorder of both their protagonists' homes and the novel form. In examining these ideas, I seek to complicate existing accounts of waste in literature, including my own, and of 1960s and 70s countercultural writing, both of which remain heavily focused on writing by male authors.